STRATEGI ASPEK PRIORITAS KOTA LAYAK HUNI (LIVABLE CITY) PADA KOTA BANDAR LAMPUNG - Yudhistira, Farhan; Putri, Marsista Buana (Jurnal Perencanaan dan Pengembangan Kebijakan, 2024)
A livable city is a comfortable condition in an urban environment to become a place for activities and a place to live by considering at two aspects, which are physical and non-physical aspect. The city of Bandar Lampung is part of the 10th bottom-tier city with a comfort index of 56% based on the Most Livable City Index (MLCI) in 2017. There are several aspects that are not feasible according to the MLCI assessment. Those five aspects are pedestrian facilities, city park facilities, development information and community participation, sewage and drainage management, and transportation. The aim of this study is to formulate a strategy on the priority aspects of livable city in Bandar Lampung using a deductive approach and data collection techniques through observation and interviews. This research is conducted by using Analytical Hierarchy Process and SWOT analysis. The result shows that the priority aspect that needs to be improved in order to make livability in Bandar Lampung is by improving sewage and drainage management. And the strategies that is formulated to improve the sewage and drainage management are optimizing routine maintenance on tertiary and secondary drainage as a preventive measure against floods, optimizing the development of Community-Based Total Sanitation to reduce pollution in drainage, and strengthening the coordination between the government and the community in environmental maintenance, especially drainage.